PENERAPAN MODEL PEMBELAJARAN INKUIRI BERBASIS KONSEP JUAL BELI TERHADAP RESPON SISWA PADA MATA PELAJARAN STATISTIKA - Fitriani Fitriani (Universitas Islam Sumatera Utara, 2018)
Abstract. Learning is the process of interaction between students and their environment so that there is a change in behavior towards a better direction. So that in generating a positive response it is necessary to improve the learning model. This research was conducted at the fifth grade IT FAZA AZKIA Elementary School, Kelurahan Hutaraja, Kabupaten Tapanuli Selatan, Provinsi Sumatera Utara. Research uses classroom action research. The study aims to determine how students respond to the use of inquiry-based learning models based on the concept of buying and selling on statistical material. This research resulted in the response of students in the first cycle still not achieving a minimum score of 80%. While the response of students in cycle second the entire response of students has reached a minimum value of 80%. So that the response of students has been positive and this has increased from cycle I to cycle II.Keywords: Student Response, Inquiry Learning Model, Buying and Selling Concept